Interactive Computer-Based Learning Media for Teaching Transformation Topic at Mathematics Class of Senior High School - Shabri, Rais; Roza, Yenita; Sakur, Sakur (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research aims to produce interactive computer based learning media for transformation topic on to be used students of class XI Senior High School. This research uses a development model by Borg and Gall that has been modified by Sugiyono. The research steps starting by information collection formulated in needs analysis. Next step is the design of product storyboard in the form of paper based and followed by computer based design. At this stage of computer-based product was designed by using Microsoft Power Point application, Adobe Photoshop application and Front Page application. Learning media is further validated by the experts which then revised based on feedback and suggestions from the the experts. Learning media that have been validated and revised were tested through small group trials and large group trials on students of MAN 1 Pekanbaru. Based on the results of data analysis and discussion can be concluded that computer based learning media interactive multimedia model for transformation topic is considered valid (3.52) and had good practicality (3.71). This application is recommended to be used by teachers for teaching Transformation topics at Senior High School if the school provided computer facilities for their learning.